Semiotics of terror: Muslim children and women in Hindu Rashtra - Sarkar, Tanika (2002)
What is new about Gujarat, it is argued here, is best exemplified by what happened to Muslim women and children on the days of the long knives. Not just their killing and the sadism that sums up the nature of ethnic cleansing, the shape of Hindu Rashtra. - Reproduced.
Keywords: Communal violence